CRIMINAL RESPONSIBILITY OF BUSINESS OPERATORS FOR IRON SAND MINING CAUSED ENVIRONMENTAL DAMAGE - Didik Irawansah; Nasrullah; Kasmar (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
The purpose of this research is first to describe the arrangement of criminal liability for business actors for iron sand mining activities which result in environmental damage; second, to describe the form of criminal responsibility of business actors for iron sand mining activities which result in environmental damage. Empirical legal research methods (non-doctrinal), case and policy approaches, using data collection, documentation, observation, and interviews and integrating with literature review of legal documents relevant to the object under study, and analyzed descriptively. The results of the study show, First, legal arrangements for criminal acts of environmental pollution committed by business actors, can be seen in Article 98, Article 99, Article 100, Article 101, Article 104, Article 105, and Article 112 of Law Number 32 of 2009 concerning Protection and Management of the Environment (UUPPLH) can be imposed on individuals, corporations, and authorized officials. Furthermore, accountability for criminal acts of environmental pollution as ultimum remedium is the last legal remedy where the goal is to punish the perpetrators in the form of imprisonment. In enforcing environmental criminal law through four stages namely investigation, prosecution, examination, and execution. In article 94 of the UUPPLH the investigators are Republic of Indonesia Police Officers and Civil Servant Officials, in article 96 evidence, the validity of evidence is witness testimony, expert testimony, letters, certain instructions, statements from the accused, as well as other evidence including evidence which is regulated in laws and regulations. Second, Forms of Corporate Criminal Liability Against Iron Sand Mining Activities Causing Environmental Damage. In the form of absolute liability (strict liability), however, based on Article 88 of the Law, absolute liability or (strict liability) is only limited to the obligation to pay compensation in the event of a civil lawsuit, on the other hand, criminal liability adhered to by the Law Number 32 of 2009 concerning Environmental Protection and Management still adheres to the principle of error.